An On-line Concurrent Test for Partial and Dynamically Reconfigurable FPGAs - Gericota, Manuel G. (2017)
The use of partial and dynamically reconfigurable FPGAs in reconfigurable systems opens exciting possibilities, since they enable the concurrent reconfiguration of part of the system without interrupting its operation. Nevertheless, larger dies and the use of smaller submicron scales in the manufacturing of this new kind of FPGAs increase the probability of failures after many reconfiguration processes. New methods of test and fault tolerance are therefore required, capable of ensuring system reliability. This paper presents improvements to our RaT Freed Resources technique, originally present in [1], a structural concurrent test approach able to detect and diagnosis faults without disturbing system operation, throughout its lifetime.